ZAKAT DALAM KAJIAN YURIDIS, PSIKOLOGIS DAN SOSIOLOGIS - Rosyad, Abdul; Kurniawan, Ade Fakih (CV Widina Media Utama, 2023)
Zakat is the issuance of part of the property with certain conditions, which Allah Almighty requires the owner to be handed over to the one who is entitled to receive it, with certain conditions as well. This study aims to examine zakat from juridical, psychological and sociological aspects. This research method uses a qualitative descriptive type of research with a type of literature research. The approaches used are juridical, psychological and sociological approaches. Testing the validity of the data with tringulation techniques. The results of the study revealed that the juridical review of zakat in Indonesia was first promulgated through Law No. 38 of 1999 concerning Zakat Management, then further affirmed with the latest Zakat Law which replaced Law 38/1999, namely Law No. 23 of 2011 concerning Zakat Management. Zakat psychologically educates humans to become altruistic and prosocial figures by involving several psychic functions, including (1) empathy, (2) spiritual intelligence, (3) emotional intelligence, (4) against the voice of truth and the voice of demons, (5) appreciation that serves as motivation, and (6) the predicate of a spiritually intelligent human figure. In a sociological perspective, zakat is one of the ways to achieve a balance of social justice in society by helping the rich, the rich helping the poor, the strong helping the weak, Zakat is one of the fundamental theories for the establishment of social structures in Islamic teachings